Negative Shocks, Job Creation, and Selection - Daniel Kopasker; Holger Görg; Hassan Molana; Catia Montagna (WWWforEurope, 2013)
High inter-country variability characterises the responsiveness of both output to (exogenous) shocks and employment to output contractions. We argue that intercountry differences in firm-size distributions contribute to explaining this variability. Within an open economy model, we show that competitive selection processes are an important channel through which a shock affects aggregate employment. Intra-industry selection is then shown to influence the effectiveness of active labour market policies in countering the employment and welfare effects of a negative shock. We estimate a measure of the shape parameter of firm size distribution and study its effect on the employment-output relationship for a number of OECD countries. Our results confirm the key predictions of the theory.
Keywords: E22; E64; F12; F41; 330; Job creation; employment subsidies; competitive selection; international trade